2020
DOI: 10.1021/jacs.0c06987
|View full text |Cite
|
Sign up to set email alerts
|

Platform to Discover Protease-Activated Antibiotics and Application to Siderophore–Antibiotic Conjugates

Abstract: Here we present a platform for discovery of protease-activated prodrugs and apply it to antibiotics that target Gram-negative bacteria. Because cleavable linkers for prodrugs had not been developed for bacterial proteases, we used substrate phage to discover substrates for proteases found in the bacterial periplasm. Rather than focusing on a single protease, we used a periplasmic extract of E. coli to find sequences with the greatest susceptibility to the endogenous mixture of periplasmic proteases. Using a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 149 publications
0
33
0
Order By: Relevance
“…Since 2013, the Miller group has shown that mixed ligand siderophore 1 , containing either a succinyl or glutaryl N -acyl-hydroxamate linker, is a versatile antibiotic, biosensor, and drug delivery vector for targeting A. baumannii with a wide variety of antibiotics that act on periplasmic targets including beta-lactams, , lipodepsipeptides, , and glycopeptides. , Attempts to utilize siderophore 1 to deliver antibiotics with cytoplasmic targets, such as fluoroquinolones, have failed, implying that this siderophore scaffold is transported to the periplasm but not the cytoplasm . Several groups, including the Miller, Nolan, and Seiple groups, have made recent advancements in developing cleavable linker systems for siderophore–antibiotic conjugates enabling pathogen-triggered drug release to expand this drug delivery technology to antibiotics with cytoplasmic targets …”
mentioning
confidence: 99%
“…Since 2013, the Miller group has shown that mixed ligand siderophore 1 , containing either a succinyl or glutaryl N -acyl-hydroxamate linker, is a versatile antibiotic, biosensor, and drug delivery vector for targeting A. baumannii with a wide variety of antibiotics that act on periplasmic targets including beta-lactams, , lipodepsipeptides, , and glycopeptides. , Attempts to utilize siderophore 1 to deliver antibiotics with cytoplasmic targets, such as fluoroquinolones, have failed, implying that this siderophore scaffold is transported to the periplasm but not the cytoplasm . Several groups, including the Miller, Nolan, and Seiple groups, have made recent advancements in developing cleavable linker systems for siderophore–antibiotic conjugates enabling pathogen-triggered drug release to expand this drug delivery technology to antibiotics with cytoplasmic targets …”
mentioning
confidence: 99%
“…In addition to the two enzymes discussed above, bacterial proteases, 171,172 nitroreductases, 173 hyaluronidases 174 and esterases, 175 etc. can also be used as triggers to design smart antimicrobial prodrugs with on-demand antimicrobial activity.…”
Section: Enzyme-triggered Antimicrobial Polymersmentioning
confidence: 99%
“…63,64 Removal of the Boc group from 84 and reacylation with a modified artemisinin gave conjugate 86. While artemisinin (87) itself is a potent antimalarial agent, it has no independent anti-TB activity. However, we anticipated that, once sequestered, the Mtb iron reductase or the resulting ferrous iron might cleave artemisinin's peroxide to form a lethal reactive oxygen species (ROS).…”
Section: ■ Development Of Common Methodologymentioning
confidence: 99%
“…During the preparation of this Account, Boyce et al reported the design of siderophore conjugates (125 and 127, Figure 8) with bacterial periplasmic protease-susceptible linkers. 87 For comparison to our earlier described β-lactamase-triggered strategy, they used the same biscatechol siderophore linked by the WSPKYM peptide to two of the same antibiotics (amino eperezolid 118 and daptomycin 121) that we had used. Microbiological assays demonstrated that the large conjugates were recognized by targeted Gram-negative bacteria (i.e., A. baumannii), and after being actively assimilated, the periplasmic protease caused cleavage at the C-terminal amino acid of the peptide linker to release the pendant drug and induce antibacterial activity.…”
Section: ■ Releasable Linkersmentioning
confidence: 99%